O senhor da ordenação : um estudo da relação entre o faraó Akhenaton e as oferendas divinas funerárias durante a reforma de Amarna (1353-1335 a. C.) - Chapot, Gisela (2007)
This paper aims to study the social and cosmic function of the the egyptian ruler stressing its relationship with the funerary and divine offerings important elements to keep the whole universe in order and balance. Like a priest of the sun , the king repulses the caos Isefet and keeps Maat (truth-justicemesure of universe-order) along all the faraonic period. Our goal here is to show how the pharao Akhenaton (1353-1335 a.C.), during the Amarna Age in the New Kingdom ( 1550 1069 a.C.) fulfilled that ritual function in one of the most important events of the ancient egyptian history: the amarna revolution.